Role of Lumican in the Corneal Epithelium during Wound Healing() - Saika, Shizuya (2000)
Lumican regulates collagenous matrix assembly as a keratan sulfate proteoglycan in the cornea and is also present in the connective tissues of other organs and embryonic corneal stroma as a glycoprotein. In normal unwounded cornea, lumican is expressed by stromal keratocytes. Our data show that injured mouse corneal epithelium ectopically and transiently expresses lumican during the early phase of wound healing, suggesting a potential lumican functionality unrelated to regulation of collagen fibrillogenesis, e.g. modulation of epithelial cell adhesion or migration. An anti-lumican antibody was found to retard corneal epithelial wound healing in cultured mouse eyes. Healing of a corneal epithelial injury in Lum(−/−) mice was significantly delayed compared with Lum(+/−) mice. These observations indicate that lumican expressed in injured epithelium may modulate cell behavior such as adhesion or migration, thus contributing to corneal epithelial wound healing.